Maximization Postulates and Their Efficacy for Islamic Economics - Zubair Hasan (American Journal of Islam and Society, 2002)
This paper examines the nature and role of maximization postulates concerning profit and utility in the mainstream price theory formation, from a methodological perspective. Mainstream economics retains these postulates, despite much criticism, mainly for two reasons. Firstly, they help establish cause-effect linkages among economic variables and markets. In that they greatly facilitate predictions and their empirical veri_fication over a wide field of inquiry. Secondly, no other behavioral rule has so far been established that gives equally valid, if not superior, results over such range. ft is argued that the postulates are required in fslamic economics as well for the same reasons. Maximization, per se, is not un-Islamic: what is maximized, how and for what purpose are the real issues to investigate before passing judgment. Contrary to the current position in the I iterature, we find it preferable to include moral values and social considerations of Islam in the assumptions of economic theorems, rather than attempting to include them in the objective elements of the models, until Islamic economics evolves as an independent subject. For maximization is a mathematical concept, and cannot fruitfully accommodate what cannot somehow be measured.